The Realationship Between Managers’ Humor Styles and Employees’ Perceptions of Organizational Culture - Ruzgar, Nilufer (European Scientific Journal, ESJ, 2019)
The workforce of Generation Z members are increasing in number, especially in the retailsector. The fact that they are young causesthem to leave their jobs easily. It is crucial to make them adopt the organizational culture so as to prevent high turnover rates. The use of appropriate style of humor in organizations can result in making this workforce adopt the organizational culture by heart. This paper focuses on examining the relationship between managers’ humor styles and organizational culture of Generation Z employees in retail sector by means of quantitative analysis. A survey form that consists of two scales and demographical questions is used. The former scale is “Humor Styles Questionnaire” (HSQ) with 32 items, which is developed by Martin and Puhlik-Doris (2003). The latter scale is “Organizational Culture Questionnaire” with 36 items, which is developed by Denison (1999). According to the findings, there is a statistically significant relationship between managers’ humor styles and Generation Z employees’ organizational culture perceptions.